Atractylodes macrocephala Root Rot Affects Microbial Communities in Various Root-Associated Niches - Huiyan Fan; Jiayi Han; Xiujuan Li; Jingzhi Zhou; Limei Zhao; Yiling Ying; Guoyin Kai (Agronomy)
Atractylodes macrocephala, a perennial herb widely used in traditional Chinese medicine, is highly prone to root rot, which significantly reduces its yield and quality. This study compared the physicochemical properties of soil from healthy and diseased A. macrocephala plants and analyzed the microbial diversity in the endophytic, rhizosphere, and root zone soils. The results showed that the diseased plants had higher levels of available potassium and electrical conductivity in the rhizosphere, both positively correlated with the severity of root rot, while soil pH was negatively correlated. The diversity and richness of endophytic bacterial and fungal communities were significantly reduced in diseased plants. Additionally, root rot led to major changes in the rhizosphere microbial community, with an increased abundance of Proteobacteria and Ascomycota, and a decrease in Firmicutes, Bacteroidetes, Actinobacteria, and Basidiomycota. Fusarium oxysporum, Fusarium solani, and Fusarium fujikuroi were identified as key pathogens associated with root rot. This study enhances our understanding of the microbial interactions in soils affected by root rot, offering a foundation for developing soil improvement and biological control strategies to mitigate this disease in A. macrocephala cultivation.